PENGARUH CASH FLOW DAN WORKING CAPITAL TERHADAP NILAI PERUSAHAAN (Studi Kasus pada Perusahaan Manufaktur Sektor Industri Dasar & Kimia dan Sektor Aneka Industri yang terdaftar di Bursa Efek Indonesia 2017 - 2019) - Nani Sriyani (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
This study aims to examine the effect of cash flow, working capital, and cash holding on firm value in manufacturing companies in the basic & chemical industrial sector and various industrial sectors listed on the Indonesia Stock Exchange (IDX) in 2017-2019. This research uses purposive sampling method in determining the research sample. The population in this study was 116 companies, with the sample used in this study as many as 33 manufacturing companies in the basic & chemical industry sector and various industrial sectors listed on the Indonesia Stock Exchange (IDX) in 2017-2019. The statistical method used in this research is using panel data regression analysis. The results of this study using the eviews 9 application show that simultaneously cash flow and working capital have a significant effect on firm value. Partially, working capital has a significant effect on firm value and while cash flow have no effect on firm value. Keywords: Cash Flow; Working Capital; Firm Value